Dynamics of defoliation of associated grasses (Research, Society and Development, 2020)
The behavior of variables related to defoliation dynamics was evaluated, and their respective oscillations in two intercropping of tropical climate grasses managed under two grazing intensities. We used pastures formed with two intercropping (BRS Zuri, Xaraés and Basilisk; BRS Quênia, Marandu and BRS Paiaguás), managed in two grazing intensities: 40 and 60% of the pre-grazing height. In the consortium between BRS Zuri, Xaraés and Basilisk, the first canonical variable explained 72.1 and 79.2% of the total variation of the defoliation pattern for the grazing intensity levels of 40 and 60%. In the consortium between BRS Quênia, Marandu and BRS Paiaguás, the first canonical variable explained 84.3 and 89.0% of the total variation of the defoliation pattern for the grazing intensity levels of 40 and 60%. The choice of forage species of tropical climate to form the consortium may be decisive in order to perpetuate plant diversity. From the population density of tillers, it is possible to observe that grasses belonging to functional groups A and B (Zuri, Xaraés, BRS Quênia and Marandu) have a higher probability of coexisting in the same area. The choice of forage species for the establishment of intercropped pastures is important to ensure the coexistence between them and the persistence of the consortium. The analysis of canonical variables assists in explaining the dynamics of defoliation of intercropping through the estimates of severity and frequency of defoliation of extended tiller and pseudostem.